2020
DOI: 10.1097/mat.0000000000001118
|View full text |Cite
|
Sign up to set email alerts
|

Food and Drug Administration Malfunction Recalls of Left Ventricular Assist Devices

Abstract: Left ventricular assist devices (LVADs) are being increasingly implanted given the increasing prevalence of patients with advanced heart failure stages. However, they are not exempt from device malfunctions. A PubMed search for the key words (left ventricular assist device malfunction) (ventricular assist system malfunction) was performed. We identified 28 publications in the US Food and Drug Administration (FDA) website database that addressed LVAD malfunction. Twenty-nine FDA recalls were identified regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…18 Corrective measures from Abbott contain a locking clip and later a redesign of the bend relief tube connection to the pump. 16 Last, a compressed outflow graft caused low flow problems in one of our patients when a blood clot wedged itself between the bend relief tube and the outflow graft. A recent study suggested resolving this stenosis with a stent.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…18 Corrective measures from Abbott contain a locking clip and later a redesign of the bend relief tube connection to the pump. 16 Last, a compressed outflow graft caused low flow problems in one of our patients when a blood clot wedged itself between the bend relief tube and the outflow graft. A recent study suggested resolving this stenosis with a stent.…”
Section: Discussionmentioning
confidence: 78%
“…Recalls from Abbott in 2014 and 2017 reported four and 26 deaths, respectively, and addressed this remaining matter of concern. 16 This is an example of a potential major malfunction because there is a pump stop of transient nature when the controller is replaced. During the years, we changed our LVAD management program to optimize patient care including; dedicated mechanical circulatory support coordinators, yearly training for our patients (with special focus on changing the controller), and stringent echocardiographic follow-up instead of only focusing at the LVAD parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation